Beyond hummus—an up-to-date scientific review of chickpeas, health, and environmental impact - Copperstone, Claire; Jones, Petra; Aydın, Betül; Zivkovic, Jelena; Can Aytar, Erdi; Kalkan Yıldırım, Hatice; Ćujić Nikolic, Nada; Künili, İbrahim Ender; Yilmaz, Ebru; Tirpanci Sivri, Goksel; Seylam Küşümler, Aylin; Özalp Ünal, Derya; et al. (Frontiers in Sustainable Food Systems, 2025)
Chickpeas (Cicer arietinum L.), form part of the pulses group and have been cultivated and consumed for many years, providing beneficial nutritional properties, whilst also being considered as sustainable foods. The global market for chickpeas is expected to continue growing because of increased consumer acceptability and growing needs for foods that support nutritional health and demand for alternative plant-based protein sources. Furthermore, these crops contribute to nitrogen fixation in soils and are therefore utilized for crop rotation systems, important in today’s need to cope with sustainability demands. Food security is a major concern, with increasing pressure to supply affordable, accessible and nutritious foods to the world’s growing population. On the other hand, challenges for chickpea consumption exist and may be in part explained by various sociocultural and economic factors, such as lack of knowledge and long preparation times, as well as the current global nutrition transition marked by increasing fast food availability and preferences. Crops like chickpeas therefore have an important role in addressing many Sustainable Development Goals (SDGs) including SDG 2 (Zero Hunger) and SDG 13 (Climate Action). Chickpeas’ nutritional profile includes protein quality, fiber, micronutrients and bioactive compound content. Antinutrients are also present, reducing nutrient bioavailability and provoking digestive health issues with some allergenic potential also observed. Mitigation techniques range from pre-cooking methods such as soaking and dehulling, as well as various cooking processes and fermentation. The latter process has been shown to improve probiotic activity and reduce phytate levels, in particular. The aim of this review is therefore to re-examine the nutritional profile for the two main chickpea types, the ‘kabuli’ and ‘desi’ types, the limitations of the antinutritional factors present, and explore techniques to mitigate these compounds. Socio-cultural and economic limitations faced by farmers will be addressed, a concern since it could further exacerbate poverty and food insecurity. Successful strategies that have improved yields will also be presented. The review will therefore present the integration of nutritional health with environmental considerations so as to deliver an updated picture for the chickpea crop and provide actionable recommendations to address the growing global population’s future needs.